"A comparison of vaginal Misoprostol with intravenous Oxytocin for cervical ripening and labor induction " - Eftekhari N; Motamedi B; Said H (Acta Medica Iranica, 2002)
Labor induction despite an unriped cervix is one of the most common indications of the use of prostaglandines. This clinical trial was performed to compare the effectiveness of oxytocin with misoprostol for induction of labor in Bahonar Hospital, Kerman/Iran from 1999 to 2000. Sixty pregnant women with indication for labor induction were randomly assigned to receive misoprostol or oxytocin. Misoprostol in tablet form. 25 µg, was placed in the posterior fornix and was repeated every four hours in the first group (to a maximum of 100 µg). The second group received intravenous oxytocin (21 µm/min). The results showed that 83.3% of women in the misoprostol group were delivered vaginally within 3.5-21 hours of the initiation of induction versus 76.7% within 4.5-17.5 hours in oxytocin group and there was no significant difference between them. The total cesarean rate was between them. The total cesarean rate was approximately similar in the two groups. Women receiving oxytocin had higher rate of cesarean for distocia (5 versus 1). The mean and median interval from induction to delivery were not significantly different between the two groups, (685±223 and 710 minutes in the first group compared with 685±198 and 690 minutes in the second group, respectively). There were no significant differences in Apgar score and meconium staining between the two groups. Hyperstimluation was seen in a patient in the first group with neither low Apgar score nor adverse neonatal outcomes. This study showed that the outcome of induction was not significantly different in the two groups. Therefore regarding the advantages of misoprostol, it is recommended as an alternative to oxytocin.